2017
DOI: 10.3389/fonc.2017.00262
|View full text |Cite
|
Sign up to set email alerts
|

The Landscape of mtDNA Modifications in Cancer: A Tale of Two Cities

Abstract: Mitochondria from normal and cancerous cells represent a tale of two cities, wherein both execute similar processes but with different cellular and molecular effects. Given the number of reviews currently available which describe the functional implications of mitochondrial mutations in cancer, this article focuses on documenting current knowledge in the abundance and distribution of somatic mitochondrial mutations, followed by elucidation of processes which affect the fate of mutations in cancer cells. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 134 publications
(178 reference statements)
1
60
0
Order By: Relevance
“…As an easily measurable and accessible proxy for mitochondrial function, mitochondrial DNA copy number (mtDNA-CN) is increasingly used to assess the role of mitochondria in disease. Several population-based studies have shown higher levels of mtDNA-CN to be associated with decreased incidence for CVD and its component parts: coronary artery disease (CAD) and stroke 2,3 ; neurodegenerative disorders such as Parkinson's and Alzheimer's 4,5 ; as well as several types of cancer including breast, kidney, liver and colorectal [6][7][8] . Furthermore, mtDNA-CN measured from peripheral blood has consistently been shown to be higher in women, decline with age, and correlate negatively with white blood cell (WBC) count [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…As an easily measurable and accessible proxy for mitochondrial function, mitochondrial DNA copy number (mtDNA-CN) is increasingly used to assess the role of mitochondria in disease. Several population-based studies have shown higher levels of mtDNA-CN to be associated with decreased incidence for CVD and its component parts: coronary artery disease (CAD) and stroke 2,3 ; neurodegenerative disorders such as Parkinson's and Alzheimer's 4,5 ; as well as several types of cancer including breast, kidney, liver and colorectal [6][7][8] . Furthermore, mtDNA-CN measured from peripheral blood has consistently been shown to be higher in women, decline with age, and correlate negatively with white blood cell (WBC) count [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…As an easily measurable and accessible proxy for mitochondrial function, mitochondrial DNA copy number (mtDNA-CN) is increasingly used to assess the role of mitochondria in disease. Several population-based studies have shown higher levels of mtDNA-CN to be associated with decreased incidence for CVD and its component parts: coronary artery disease (CAD) and stroke [2,3]; neurodegenerative disorders such as Parkinson's and Alzheimer's [4,5]; as well as several types of cancer including breast, kidney, liver and colorectal [6][7][8]. Furthermore, mtDNA-CN measured from peripheral blood has consistently been shown to be higher in women, decline with age, and correlate negatively with white blood cell (WBC) count [9][10][11].…”
mentioning
confidence: 99%
“…[43], Hertweck et al . [44], as well as the MITOMAP database [45] for readers interested in potential mtDNA drivers of cancer. For example, some reports suggest that the mutational frequency was higher within the hypervariable D-Loop [25,4648].…”
Section: Mitochondrial Dna and Cancermentioning
confidence: 99%